The Royal Villa Resort: Taking over Dad’s Business (Global Business Management Review (GBMR), 2022)
‘The Royal Villa Resort: Taking over Dad’s Business’- is a case which discusses the dilemma of a second generation entrepreneur Vipin Soni, who gets involved in the business due to the sudden death of his father. After taking a stock of the situation, he is exploring the different options to make the business profitable. The case is about analyzing the scenario and challenges of hotel industry in a two- tier city in India. It also explores the various strategic options in the hospitality industry to run a business successfully. The case will be useful for students of business administration, management and students specializing in the field of marketing, tourism marketing and hotel management. This case can be a useful tool in teaching the concepts like 7Ps of service marketing, franchising, marketing strategy, etc. while exposing the students to the competitive scenario in hotel and tourism industry. The methodology followed for writing the case is qualitative in nature. In-depth interviews have been conducted to get insights into the business. The various published reports by Indian Tourism Industry have been mapped with the context to make it useful for teaching the said concepts.